(untitled) (Perner’s Contacts, 2020)
Electromobility is a preferred way of car manufacturers to deal with environmental impact of their products. But is it also a preferred way of their customers? This paper gives insights on history of electromobility, EU market incentives, customers’ approaches towards innovative products in automotive and plans for Clean mobility in the Czech Republic. Finally it presents motivational factors of buying electric cars amongst Prague University of Economics and Business students.